Adolescent alcohol consumption produces long term changes in response inhibition and orbitofrontal-striatal activity in a sex-specific manner - Aqilah M. McCane; Lo Kronheim; Bita Moghaddam (Developmental Cognitive Neuroscience)
Alcohol use disorder (AUD) is strongly associated with initiation of drinking during adolescence. Little is known about neural mechanisms that produce the long-term detrimental effects of adolescent drinking. A critical feature of AUD is deficits in response inhibition, or the ability to withhold a reward-seeking response. Here, we sought to determine if adolescent drinking affects response inhibition and encoding of neural events by the orbitofrontal cortex (OFC) and dorsomedial striatum (DMS), two regions critical for expression of response inhibition. Adolescent male and female rats were given access to alcohol for four hours a day for five consecutive days. Then, rats were tested in a cued response inhibition task as adolescents or adults while we recorded concomitantly from the OFC and DMS. Adolescent voluntary alcohol drinking impaired response inhibition and increased alcohol drinking in male but not female rats. Adolescent alcohol drinking was associated with reduced excitation following premature actions in adults and increased OFC-DMS synchrony in male but not female rats. Collectively, these data suggest sex-specific effects of adolescent alcohol drinking on response inhibition and corresponding alterations in cortical-striatal circuitry.